2015
DOI: 10.5586/am.1055
|View full text |Cite
|
Sign up to set email alerts
|

Micromycetes on ericaceous plant leaves

Abstract: A two-year study was carried out on the ericaceous plant collection of the Botanic Garden of the Jagiellonian University in Cracow and the Rogów Arboretum of the Warsaw University of Life Sciences on the following plants: wild rosemary Ledum palustre L., leatherleaf Chamaedaphne calyculata (L.) Moench and American cranberry Oxycoccus macrocarpus (Ait.) Pursh. Diverse micromycetes species composition was specified on the leaves of tested ericaceous plants. The perpetrators of dying leaves were recognized, among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Thirty-five percent of them were included in the genera Trichoderma, Para-leaf blight [64,65]. According to the literature, A. alternata was identified on the leaves of cranberry plants in a Kraków botanical garden [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-five percent of them were included in the genera Trichoderma, Para-leaf blight [64,65]. According to the literature, A. alternata was identified on the leaves of cranberry plants in a Kraków botanical garden [15].…”
Section: Discussionmentioning
confidence: 99%
“…Figure15. Phylogenetic tree of American cranberry isolates most similar to Aspergillus fumigatus constructed with partial sequences of the ITS region (566 bp).…”
mentioning
confidence: 99%
“…ey were isolated from leaves with discolorations, spots, and necrosis. Species from the genera were recorded in samples of atmospheric air and leaves of Ericaceae plants in both the Botanic Garden of the Jagiellonian University in Cracow and the Rogów Arboretum of the WULS-SGGW Kowalik et al, 2014aKowalik et al, , 2014bKowalik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[37], and Chamaedaphne calyculata (L.) Moench. [38]. Research into the pathogenicity of isolates from alfalfa on other hosts showed that the alfalfa isolates have greater pathogenicity towards the host from which they were isolated than towards other hosts [25,34].…”
Section: Host Ranges Of P Medicaginismentioning
confidence: 99%